ChemInform Abstract: Structural Analogues of Umifenovir. Part 1. Synthesis and Biological Activity of Ethyl 5‐Hydroxy‐1‐methyl‐2‐ (trans‐2‐phenylcyclopropyl)‐1H‐indole‐3‐carboxylate. Issue 51 (23rd December 2014) - Balzarini, J.; Ruchko, E. A.; Zakharova, E. K.; Kameneva, I. Yu.; Nawrozkij, M. B.
Abstract The title compound (VI) does not exhibit any marked antiviral activity.